2020
DOI: 10.3390/nu12051370
|View full text |Cite
|
Sign up to set email alerts
|

Daily Coffee and Green Tea Consumption Is Inversely Associated with Body Mass Index, Body Fat Percentage, and Cardio-Ankle Vascular Index in Middle-Aged Japanese Women: A Cross-Sectional Study

Abstract: This study aimed to investigate the links between coffee (CF)/green tea (GT) consumption and body composition/cardiovascular parameters in middle-aged Japanese women. We conducted a cross-sectional study of 232 Japanese women aged 40–65 years who had been referred to the menopause clinic of Tokyo Medical and Dental University Hospital between November 2007 and August 2017. Body composition, cardiovascular parameters, and CF/GT consumption frequency were evaluated on their initial visits, using a body compositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 32 publications
1
27
0
2
Order By: Relevance
“…22 The anti-obesogenic effects of different types of tea and their bioactive compounds have been described at an anthropometric and biochemical level. 22,[31][32][33][34][35][36][37][38][39][40][41] According to the latest in vitro and animal studies, the main effects described were to decrease lipid absorption and to increase fat oxidation, thus reducing triglyceride, cholesterol and leptin and to stimulate energy expenditure. 22,[32][33][34][35][36] In epidemiological studies the main effects described were a reduction in body weight, variation of body mass index, a decrease of waist/hip ratio, and a reduction of visceral and body fat.…”
Section: Effects On Lipolysis and Obesitymentioning
confidence: 99%
See 2 more Smart Citations
“…22 The anti-obesogenic effects of different types of tea and their bioactive compounds have been described at an anthropometric and biochemical level. 22,[31][32][33][34][35][36][37][38][39][40][41] According to the latest in vitro and animal studies, the main effects described were to decrease lipid absorption and to increase fat oxidation, thus reducing triglyceride, cholesterol and leptin and to stimulate energy expenditure. 22,[32][33][34][35][36] In epidemiological studies the main effects described were a reduction in body weight, variation of body mass index, a decrease of waist/hip ratio, and a reduction of visceral and body fat.…”
Section: Effects On Lipolysis and Obesitymentioning
confidence: 99%
“…22,[32][33][34][35][36] In epidemiological studies the main effects described were a reduction in body weight, variation of body mass index, a decrease of waist/hip ratio, and a reduction of visceral and body fat. 22,32,[37][38][39][40][41] White tea extracts are able to modulate the metabolic syndrome, particularly by improving lipid metabolism. 33 These extracts significantly reduced apolipoprotein B and modulated cholesterol and triglyceride levels by reducing the production of low-density lipoproteins.…”
Section: Effects On Lipolysis and Obesitymentioning
confidence: 99%
See 1 more Smart Citation
“…Yonekura et al [ 51 ] conducted a cross-sectional study in 232 Japanese women aged 40–65 years and found that daily coffee consumption was inversely associated with high BMI (adjusted OR: 0.14, CI: 0.14, 0.96) and body fat percentage (adjusted OR: 0.33, CI: 0.14, 0.82).…”
Section: The Effects Of Coffee/cga On Obesitymentioning
confidence: 99%
“…Recently, one study reported that daily consumption of coffee or green tea was inversely associated with body composition and cardiovascular parameters in middle-aged Japanese women [ 3 ]. Coffee is considered one of the most widely consumed beverages worldwide, and several studies have associated coffee consumption with lower risks of metabolic syndrome [ 4 ] and obesity [ 5 ].…”
Section: Introductionmentioning
confidence: 99%